Uso do design thinking na análise de aplicativos educacionais para crianças com transtorno de déficit de atenção e hiperatividade - Paulo, Samylly Pires (2025)
Mobile applications have been part of people’s daily lives for at least 10 years. With the advancement of smartphones, it has become increasingly easier to access various types of information. As a result, children have access to these applications from a very young age. Among the thousands of applications available, there are educational applications that help children of different ages learn while they are playing. Children with attention deficit hyperactivity disorder have difficulties learning at the beginning of their educational life, so some applications are great allies in the initial phase of learning. This study analyzed two learning applications, according to the heuristics proposed by (ABREU, 2017), which analyzes educational mobile applications for children, with the purpose of identifying possible barriers through the usability of the applications. With the help of design thinking, it was possible to propose improvements to the applications by improving the interface, adding a points program to motivate the child, and daily challenges. With the results obtained, it was possible to promote important insights into the usability of applications and more intuitive interfaces, thus reinforcing the importance of user-centered methodologies in the design of educational products.